2017
DOI: 10.1136/annrheumdis-2016-209133corr1
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Eular/ERA-EDTA recommendations for the management of ANCA-associated vasculitis

Abstract: In this article, the 2009 European League Against Rheumatism (EULAR) recommendations for the management of antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) have been updated. The 2009 recommendations were on the management of primary small and medium vessel vasculitis. The 2015 update has been developed by an international task force representing EULAR, the European Renal Association and the European Vasculitis Society (EUVAS). The recommendations are based upon evidence from systematic l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Patients are able to receive online health services such as consultations, disease education and preliminary treatment suggestions through the telemedicine platforms with audio and video settings in the communities around the province. Our previous study has demonstrated that GOH provided a convenient platform for ankylosing spondylitis patients to receive effective disease management, especially those in the remote areas of the country [ 14 ]. The positive results encourage us to explore the role of GOHT telemedicine in the management of OA.…”
Section: Introductionmentioning
confidence: 99%
“…Patients are able to receive online health services such as consultations, disease education and preliminary treatment suggestions through the telemedicine platforms with audio and video settings in the communities around the province. Our previous study has demonstrated that GOH provided a convenient platform for ankylosing spondylitis patients to receive effective disease management, especially those in the remote areas of the country [ 14 ]. The positive results encourage us to explore the role of GOHT telemedicine in the management of OA.…”
Section: Introductionmentioning
confidence: 99%
“…The specific manifestations of the following organ involvement were retrieved: renal, ear, nose, throat (ENT), pulmonary, constitutional symptoms, central nervous system, dermatological, gastrointestinal, ophthalmologic, and cardiac. The disease staging was assessed according to the European Vasculitis Society guidelines 15 as "limited" with upper and / or lower respiratory tract disease without any other systemic involvement or constitutional symptoms; "early systemic" without any organ involvement or life-threatening disease; "systemic" with kidney-or other organ -threatening disease, serum creatinine level below 500 μmol/l (5.6 mg/dl); or "severe" with kidney or other vital organ failure, serum creatinine above 500 μmol/l. 12 Vasculitis the pathogenesis of AAV is not completely understood, it is thought to be multifactorial.…”
mentioning
confidence: 99%